Implementasi Sangu Lirboyo terhadap Pembentukan Karakter Santri: Studi Kasus di Pondok Pesantren Lirboyo Kediri - Yasin Nurfalah; Syam, Nur; Chumaidi, Anis (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study examines the dynamics of character education in the implementation of Sangu Lirboyo, a cashless system at the Lirboyo Islamic Boarding School in Kediri. As the largest salaf Islamic boarding school in Indonesia, Lirboyo Islamic Boarding School not only maintains the tradition of classical Islamic knowledge, but also integrates modern technology to improve efficiency and transparency. This study uses a descriptive qualitative approach with a case study method, including observation, in-depth interviews, and document analysis. The research findings show that the implementation of Sangu Lirboyo is not only aimed at improving the efficiency of financial transactions, but also as a means of character education for students. Through this system, students are taught the values ​​of honesty, responsibility, and discipline in managing finances and permits. Guardians of students can monitor students' expenses and activities through digital applications, thus encouraging transparency and accountability.